Biliary Complications After Liver Transplantation in the United States: Changing Trends and Economic Implications. Issue 5 (22nd April 2023) - Manay, Priyadarshini; Seth, Abhinav; Jackson, Kyle; Lentine, Krista L.; Schnitzler, Mark A.; Xiao, Huiling; Segev, Dorry L.; Axelrod, David A.
Abstract : Background: Biliary complications (BCs) continue to impact patient and graft survival after liver transplant (LT), despite improvements in organ preservation, surgical technique, and posttransplant care. Real-world evidence provides a national estimate of the incidence of BC after LT, implications for patient and graft outcomes, and attributable cost not available in transplant registry data. Methods: An administrative health claims–based BC identification algorithm was validated using electronic health records (N = 128) and then applied to nationally linked Medicare and transplant registry claims. Results: The real-world evidence algorithm identified 97% of BCs in the electronic health record review. Nationally, the incidence of BCs within 1 y of LT appears to have improved from 22.2% in 2002 to 20.8% in 2018. Factors associated with BCs include donor type (living versus deceased), recipient age, diagnosis, prior transplant, donor age, and donor cause of death. BCs increased the risk-adjusted hazard ratio (aHR) for posttransplant death (aHR, 1.43; P  < 0.0001) and graft loss (aHR, 1.48; P  < 0.0001). Nationally, BCs requiring intervention increased risk-adjusted first-year Medicare spending by $39 710 ( P  < 0.0001). Conclusions: BCs remain an important cause of morbidity and expense after LT and would benefit from a systematic quality-improvement program.